The gendered impacts of income fluctuations on household departure, labor supply, and human capital decisions: Evidence from Kyrgyzstan - Kosec, Katrina; Song, Jie; Zhao, Hongdi; Holtemeyer, Brian (Informa UK Limited, 2023)
How do fluctuations in income affect labor supply decisions, and how do their effects differ by gender? This study analyzes data from a thirteen-year rolling panel in Kyrgyzstan spanning 2004–16. It addresses the endogeneity of fluctuations in income to labor supply decisions by employing shift share instruments that exploit region-level changes over time in growth rates of different sources of revenue and production costs. Estimating a household fixed effects model, the study finds that reductions in income relative to the median spur departure from the household (for example, due to migration), with smaller impacts on women than men. However, women’s labor supply at the origin is affected significantly more, with short-term increases in hours of employment and declines in home production and other activities. Reductions in income also fuel temporary migration for both genders, with larger effects for men, and widen the gender gap in pursuit of non-compulsory education.